Cartas pedagógicas freireanas: uma revisão sistemática de literatura - (:unkn) unknown (Universidade Federal do Pampa, 2026)
This study investigates the Pedagogical Letters, a communication tool used by Paulo Freire, a renowned educator, in his dialogical and emancipatory approach to education. Although originating in his pedagogical practice, the term Pedagogical Letters was consolidated posthumously to refer to these practices. In response to the structural challenges of the Brazilian educational system, this research seeks to answer how Pedagogical Letters can be employed as a research tool, promoting an inclusive, critical, and transformative pedagogy. The aim is to analyze the methodological contribution of these letters, mapping recent studies and examining their applications in different educational contexts. This qualitative, exploratory bibliographic research employs a systematic literature review to deepen understanding of the role of Pedagogical Letters in education. The study is justified by the need to explore how this methodological approach, integrating theory and practice, can enhance educational research as well as pedagogical practices in Brazil. The results indicate that Pedagogical Letters are predominantly employed in teacher training contexts, Youth and Adult Education, and popular education, functioning as a tool for reflective writing, qualitative data production, and pedagogical mediation. The analyzed studies demonstrate that this tool facilitates the articulation between theory and practice, strengthens teacher identity, values students’ knowledge, expands dialogical engagement, and fosters the development of critical consciousness. Furthermore, Pedagogical Letters show potential as an ethical and participatory research strategy, promoting more horizontal relationships between researchers and participants. It is therefore concluded that Pedagogical Letters constitute a powerful methodological instrument for qualitative research in education, aligned with Freirean pedagogy, contributing to the production of situated knowledge and the strengthening of emancipatory educational practices.
Freirean pedagogical letters: a systematic literature review
Keywords: Escrita reflexiva; Legado de Paulo Freire; Metodologia autoral; Pedagogia crítica; Pesquisa em educação; Reflective writing; Paulo Freire’s legacy; Authorial methodology; Critical pedagogy; Educational research; CIENCIAS HUMANAS